Use of base metal casting alloys for implant framework: marginal accuracy analysis (Journal of Applied Oral Science, 2004)
The original protocol for implant prosthesis recommends the use of a gold framework for acrylic and ceramic prosthesis. However, due to its high cost, the use of alternative alloys is desired. This study compares the marginal accuracy of pre-made cylinders versus plastic cylinders cast with two different base metal casting alloys. Five samples each of (1) plastic cylinder cast in cobalt-chromium alloy, (2) plastic cylinder cast in nickel-chromium alloy, and (3) silver-palladium pre-made cylinder (control) were examined for marginal accuracy according to: (A) vertical gap; (B) horizontal gap and (C) horizontal gap depth at the abutment/cylinder interface. Data were submitted to statistical analysis (ANOVA and Student-Newman Keuls, p